2014
DOI: 10.1002/2013jc009533
|View full text |Cite
|
Sign up to set email alerts
|

The Indonesian Throughflow response to Indo‐Pacific climate variability

Abstract: The Indonesian Throughflow (ITF) is the only open pathway for interocean exchange between the Pacific and Indian Ocean basins at tropical latitudes. A proxy time series of ITF transport variability is developed using remotely sensed altimeter data. The focus is on the three outflow passages of Lombok, Ombai, and Timor that collectively transport the entire ITF into the Indian Ocean, and where direct velocity measurements are available to help ground-truth the transport algorithm. The resulting 18 year proxy ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 61 publications
6
139
0
Order By: Relevance
“…The INSTANT estimates also reveal inter-annual fluctuation; see Table 1 of Gordon et al (2010). Nevertheless, Sprintall and Revelard (2014) argue that the 3-year time series alone is not sufficient to comprehensively resolve the inter-annual signal. In the INDO12 simulation, Fig.…”
Section: Volume Transport (Itf and Scstf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The INSTANT estimates also reveal inter-annual fluctuation; see Table 1 of Gordon et al (2010). Nevertheless, Sprintall and Revelard (2014) argue that the 3-year time series alone is not sufficient to comprehensively resolve the inter-annual signal. In the INDO12 simulation, Fig.…”
Section: Volume Transport (Itf and Scstf)mentioning
confidence: 99%
“…In this case, the ITF transport is reduced with the weakest transport in Ombaï and the negative IOD seems to prevail. In a recent paper, Sprintall and Revelard (2014) argue that Indian Ocean dynamics likely win out over the Pacific Ocean dynamics during concurrent ENSO and IOD events. Indeed, the ITF transport variability would be linked both to spatial patterns of SLA and to zonal wind stress anomalies.…”
Section: Volume Transport (Itf and Scstf)mentioning
confidence: 99%
“…2). It was suggested that the Indian Ocean Dipole may have strong impact on the ITF transport through the Lombok and Ombai Straits (Potemra and Schneider 2007;Sprintall and Révelard 2014).…”
Section: The Itf Transport and Its Interannual And Decadal Variationsmentioning
confidence: 99%
“…The currents and wave processes in the Makassar Strait and Spermonde Archipelago are strongly modulated by marked reversals in monsoon winds toward the southeast during the boreal winter (Dec-Feb) and northwest in summer (Jun-Aug). The Makassar Strait also acts as the major conduit of the Indonesian Throughflow (ITF), the arterial pathway connecting the Pacific and Indian oceans, and which plays a critical role in the coupled ocean and climate system (Gordon et al, 1999(Gordon et al, , 2003Gordon, 2005;Sprintall and Revelard, 2014). The ITF dynamics in the Makassar Strait are modulated by the monsoonal wind patterns.…”
Section: Oceanographic Regimementioning
confidence: 99%